2020
DOI: 10.1007/s13205-020-02351-w
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis in intestinal microbiome linked to fecal blood determined by direct hybridization

Abstract: The important physiological and pathophysiological roles of intestinal human microbiome (HMB) in human health have been emerging, owing to the access to molecular biology techniques. Herein we evaluated, for the first time, the intestinal HMB through direct hybridization approach using n-counter flex DX technology which bypasses the amplification procedure currently applied by other technologies to study the human microbiome. To this purpose, a clinical study was carried out on fecal samples, recruiting both h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…The mammalian gastrointestinal microbiota makes important contributions to the health of the host, including immune system development, nutrient metabolism and absorption, drug metabolism as well as protection against infection [ 57 ]. An altered microbiota (dysbiosis) has been associated with human diseases, such as diabetes, obesity, inflammatory bowel diseases, fecal occult blood and colorectal cancer [ 57 , 58 , 59 ]. By the way, diet is also considered a key modulator of the composition and function of the gut microbiota.…”
Section: Resistant Starch In Human Nutritional Intervention Studies: Gi and Impact On Inflammation And Gut Microbiomementioning
confidence: 99%
“…The mammalian gastrointestinal microbiota makes important contributions to the health of the host, including immune system development, nutrient metabolism and absorption, drug metabolism as well as protection against infection [ 57 ]. An altered microbiota (dysbiosis) has been associated with human diseases, such as diabetes, obesity, inflammatory bowel diseases, fecal occult blood and colorectal cancer [ 57 , 58 , 59 ]. By the way, diet is also considered a key modulator of the composition and function of the gut microbiota.…”
Section: Resistant Starch In Human Nutritional Intervention Studies: Gi and Impact On Inflammation And Gut Microbiomementioning
confidence: 99%
“…Here, we showed that a diet featuring 10% steamed broccoli sprouts reduced the Disease Activity Index and prevented DSS-induced shift in bacterial community structures along the intestines. This included preventing a shift in the microbial community caused by fecal blood, which can increase the abundance of pathobionts and reduce commensals (58, 59).…”
Section: Discussionmentioning
confidence: 99%
“…Como a AR é uma doença inflamatória e autoimune, em que quadros de disfunção e/ou inflamação intestinal podem ser determinantes para sua expressão, dados respectivos à presença de muco e/ou coloração escura nas fezes foram colhidos para verificar fatores complementares que pudessem contribuir com a apresentação da enfermidade. O perfil sintomatológico fecal constitui importante cofator para auxiliar na determinação da presença ou ausência de quadros disbióticos, doenças e/ou outras disfunções intestinais que possam provocar liberação de biomarcadores pró-inflamatórios (Holers et al, 2022;Swidsinski et al, 2008;Cafiero et al, 2020). Entretanto, a maioria dos participantes relatou ausência de muco e/ou coloração escura nas fezes.…”
Section: Discussionunclassified